LINGUISTIC COMPETENCE AS AN IMPORTANT COMPONENT OF TEACHING ACTIVE METHODS IN READING - Rubtsova, Svitlana (International Journal of Innovative Technologies in Social Science, 2021)
The article deals with the applying of active methods in reading and the formation of linguistic competence for teaching English for specific purposes (ESP) to future bachelors in the field of Civil Engineering.Purpose of the research is to describe linguistic competence as an important component of the process of teaching active methods in reading to future engineers, to define some active methods in reading that can be implemented in the teaching of ESP in the process of training future civil engineers.Methods. Reviewing the studies on linguistic competence in reading in the process of teaching ESP and methods of active reading.Results. Prospects for teaching methods of active reading (KWL and SQ3R) to future engineers in the ESP teaching process are described. The definition of lexical competence and its components in the process of teaching methods of active reading is given. The difficulties of teaching active reading in ESP for students of technical specialties are determined.Conclusion. Taking into account that creativity and active participation are important factors in motivating students to learn ESP, we consider it appropriate to use methods of active reading (KWL and SQ3R) in combination with other intensive methods and technologies to train future engineers. We believe that exercises and tasks with different forms and models of authentic visualization of educational information (AVEI) for learning English vocabulary in professionally oriented reading are effective. AVEI, taken from professional articles and other authentic materials in the field of civil engineering, can contribute to the formation of lexical competence of students.